Numerical investigation of heat and mass transfer inside a wet cooling tower - Blecich, Paolo (Array, 2018)
This paper presents a numerical investigation of heat and mass transfer inside a wet cooling tower with forced air draft, which find application in energy process industries and oil refineries. The mathematical model consists of mass, momentum and energy conservation equations, water droplet trajectories and their interaction with the gas phase, the computational domain and boundary conditions. Numerical distributions of air velocity, air temperatures, water vapor fractions and evaporation rates are shown and discussed. The wet cooling tower achieves an efficiency of around 80%, which can be improved by optimizing the value of the water droplet size, nozzle spray angle and water-to-air flow rate ratio. The water droplet size has a dominant effect on the cooling tower efficiency, whereas small droplets improve the efficiency up to 10%. On the other hand, the spray angle and the water-to-air ratio lead to slight improvements, about 2-3% in the best case.